Maintstreaming the work of legislative staff towards acheiving MDGs - Civil Society Legislative Advocacy Centre (Abuja, Nigeria : Civil Society Legislative Advocacy Centre, 2008)
The book is an account of the one-day capacity building workshop for the staff of the National planning and MDGs Committees of the National Assembly and other workshops on MDGs organized by Civil Society Legislative Advocacy Centre.
At head of title: CISLAC
"Civil Society Legislative Advocacy Centre; National Democratic Institute; United Nations Millennium Campaign"--T.p.
oif 17/07/2018
Loans
Keywords: Economic development; Millennium Development Goals; Economic development--Planning; Economic policy; Economic policy--Planning; Nigeria